The Effectiveness of Blended Learning Teaching Materials Based on Cognitive Styles to Improve Students’ Learning Outcomes in Solid State Physics Subjects - prayekti, prayekti (Advances in Social Sciences Research Journal, 2020)
The industrial revolution 4.0 forces various sectors, including the education sector, to face rapid technological innovation changes. Universitas Terbuka, as a distance learning activity management system, has made information and communication technology a fundamental requirement for implementing learning activities at UT or PTJJ. Blended learning emerges as an effective strategy that can combine the advantages of online education or technology-based learning and face-to-face learning. This study aimed to analyze the effectiveness of blended learning teaching materials based on cognitive styles to improve students’ learning outcomes in solid-state physics subjects. This research is quasi-experimental research conducted in 3 Universitas Terbuka; those are Universitas Terbuka of Surabaya, Malang, and Jember. In this study, Respondents were 11 students who were treated with blended learning teaching materials in solids state physics subjects. The data obtained are in the form of students’ learning outcomes, which are then analyzed using the N-gain test. Based on the N-gain test, the test result was accepted that the average N-gain of students was categorized as medium and high. In addition to learning outcomes, data on student responses, and learning activities were also obtained using blended learning teaching materials in solids state physics subjects. The majority of students respond to learning activities with a positive response, and students actively participate in all the learning activities provided. This study implies that blended learning materials based on cognitive styles effectively improve students’ learning outcomes in solid-state physics subjects.